Serum metabolomic analysis reveals key metabolites in drug treatment of central precocious puberty in female children - Chen, Guo-you; Wang, Li-zhe; Cui, Yue; Liu, Jin-cheng; Wang, Li-qiu; Wang, Long-long; Sun, Jing-yue; Liu, Chang; Tan, Hai-ling; Li, Qi; Jin, Yi-si; Xu, Zhi-chun; et al. (Frontiers in Molecular Neuroscience, 2023)
Precocious puberty (PP) is a common condition among children. According to the pathogenesis and clinical manifestations, PP can be divided into central precocious puberty (CPP, gonadotropin dependent), peripheral precocious puberty (PPP, gonadotropin independent), and incomplete precocious puberty (IPP). Identification of the variations in key metabolites involved in CPP and their underlying biological mechanisms has increased the understanding of the pathological processes of this condition. However, little is known about the role of metabolite variations in the drug treatment of CPP. Moreover, it remains unclear whether the understanding of the crucial metabolites and pathways can help predict disease progression after pharmacological therapy of CPP. In this study, systematic metabolomic analysis was used to examine three groups, namely, healthy control (group N, 30 healthy female children), CPP (group S, 31 female children with CPP), and treatment (group R, 29 female children) groups. A total of 14 pathways (the top two pathways were aminoacyl–tRNA biosynthesis and phenylalanine, tyrosine, and tryptophan biosynthesis) were significantly enriched in children with CPP. In addition, two short peptides (His-Arg-Lys-Glu and Lys-Met-His) were found to play a significant role in CPP. Various metabolites associated with different pathways including amino acids, PE [19:1(9Z)0:0], tumonoic acid I, palmitic amide, and linoleic acid–biotin were investigated in the serum of children in all groups. A total of 45 metabolites were found to interact with a chemical drug [a gonadotropin-releasing hormone (GnRH) analog] and a traditional Chinese medicinal formula (DBYW). This study helps to understand metabolic variations in CPP after drug therapy, and further investigation may help develop individualized treatment approaches for CPP in clinical practice.